Penggunaan Barcode pada Tanda Tangan Notaris Dilihat dari Perspektif Teori Kepastian Hukum - Nuzul Shinta Nur Rahmasari; Mohammad Saleh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
With the development of an increasingly advanced era towards the digital to minimize the use of paper. Many things have switched to use technological sophistication to simplify what is being done, this happens in various sectors. Electronic signatures as part of the renewal of notarial law in Indonesia are part of cyber notary. The concept of cyber notary provides a legal frame, namely that the act of facing the parties or the appearers before the notary no longer has to meet in-person (face to face) in a certain place. Some rules that provide convenience to notaries actually clash with the obligation of a notary who requires to sign the minutes of the deed by presenting the parties in person. Article 16 of the UUJN letter m stipulates that the notary is obliged to read out the deed in front of the appearer in the presence of at least 2 (two) witnesses, or 4 (four) witnesses specifically for the making of an underhand testament deed, and signed at that time by the appearer, witnesses and notary. The type of this research is normative juridical which aims to find legal rules and norms to answer the legal issues at hand so that problem solving can be found related to the issues that have been studied. A deed of relaas made by a notary is possible for the notary to sign it electronically but it is different if what is made by a notary is a deed of partij, which is not possible to apply an electronic signature on it because it is still constrained by regulations.